2018
DOI: 10.15446/cuad.econ.v37n75.68913
|View full text |Cite
|
Sign up to set email alerts
|

Customer perceived value in high growth firms

Abstract: Scholars have asserted that a key factor that differentiates high growth firms (HGFs) from other firms is their ability to create value for their customers. This paper contributes to the literature by empirically exploring this relationship. Drawing on comparative cohorts of eleven HGFs and ten non-HGFs in Scotland, this paper finds that the HGFs were much more likely than their non-HGF counterparts to be positively influencing customer perceived value, which is considered as an important enabler of firm perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
0
4
0
2
Order By: Relevance
“…Another study by Blackburn et al (2013) found HGFs had a higher propensity of formalising their growth intentions by developing strategic growth plans and communicating them internally. The central role of market orientation and close customer/end-user engagement was also reported in studies of Scottish HGFs which showed that by working closely with their customers, these firms ensured that their innovation processes and outcomes closely matched the requirements of the end-users (Mason and Brown, 2013;Mawson, 2018). Cases of high growth are often found to be driven by market opportunity exploitation whereas firmenvironment misalignment typically characterises low-growth firms (Yoruk and Jones, 2023).…”
Section: Empirical Studies and Rapid Firm Growthmentioning
confidence: 78%
See 2 more Smart Citations
“…Another study by Blackburn et al (2013) found HGFs had a higher propensity of formalising their growth intentions by developing strategic growth plans and communicating them internally. The central role of market orientation and close customer/end-user engagement was also reported in studies of Scottish HGFs which showed that by working closely with their customers, these firms ensured that their innovation processes and outcomes closely matched the requirements of the end-users (Mason and Brown, 2013;Mawson, 2018). Cases of high growth are often found to be driven by market opportunity exploitation whereas firmenvironment misalignment typically characterises low-growth firms (Yoruk and Jones, 2023).…”
Section: Empirical Studies and Rapid Firm Growthmentioning
confidence: 78%
“…Furthermore, as the accounts below demonstrate, just under half of the HGFs (8 of 20) reported using their “industry contacts” to “get a foot in the door” to acquire their first customers. The speed at which the HGFs gained “quality customers” was described as having a substantive positive impact on internal confidence and enhanced external credibility, thus acting as a springboard to high growth (Mawson, 2018). Conversely, a small group of young HGFs (2 of 20) whose founders had less industry experience identified their lack of “industry contacts” and “networks” as a significant inhibitor of growth.We looked to leverage pre-existing relationships, one of the co-founders is a good example.…”
Section: Findings: the Role Of Founders In The Growth Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Por estos motivos, las empresas buscan la creación del valor con el fin de obtener una ventaja competitiva significativa, debido a que es de suma importancia dentro de un proceso comercial, porque permite generar un desarrollo financiero (Mawson, 2018).…”
Section: La Responsabilidad Social Empresarial Y El Valor Percibidounclassified
“…En cuanto a la dimensión social, algunas de las exigencias del mercado son: la equidad social [8], condiciones dignas para los trabajadores [9], comercio justo [10], trabajo infantil [11], [12], protección a los consumidores [13], impacto en la comunidad [14]. La dimensión económica busca la generación de utilidades para la empresa [15], prácticas empresariales de colaboración [16], [17], adaptación al entorno [18], tecnología, gestión e innovación [19], [20], administración del conocimiento [21] [22]. Con respecto a la dimensión ambiental, las peticiones del mercado claman que se lleve a cabo una gestión ambiental eficiente [23], cumplimiento de normas [24], control de emisiones al suelo, agua y aire [25], [26], cuidado del medio ambiente [27].…”
Section: Introductionunclassified